Fear and hope : three generations of the Holocaust - Bar-On, Dan 1938-2008 (Harvard Univ. Press, 1995)
Genia spent two years in Auschwitz. Ze'ev fought with the Partisans. Olga hid in the Aryan section of Warsaw. Anya fled to Russia. Laura lived in Libya under the Italian fascist regime. All five survived the Holocaust, immigrated to Israel, and started families there. How the traumatic experience of these survivors has been transmitted, even transformed, from one generation to the next is the focus of Fear and Hope. From survivors to grandchildren, members of these families narrate their own stories across three generations, revealing their different ways of confronting the original trauma of the Holocaust. Dan Bar-On's biographical analyses of these life stories identify several main themes that run throughout: how family members reconstruct major life events in their narratives, what stories remain untold, and what is remembered and what forgotten. Together, these life stories and analyses eloquently explore the inter-generational reverberations of the Holocaust, particularly the ongoing tension between achieving renewal in the present and preserving the past.